EVOLVING STRATEGIES: INDIA'S ECONOMIC DIPLOMACY IN THE GLOBAL ERA - Nandy, Debasish (UIN Sunan Gunung Djati Bandung, 2024)
Â This study explores the evolution and strategies of India's economic diplomacy from 1991 to the present, focusing on Japan's role within the Special Strategic and Global Partnership framework. It highlights the transformation of India's economic policies due to globalization and emphasizes the significance of the partnership with Japan through key initiatives like the Delhi-Mumbai Industrial Corridor and the Mumbai-Ahmedabad High-Speed Rail project. The research identifies strategic measures taken by India to enhance economic competitiveness and address sustainability challenges. Despite progress, issues such as reliance on foreign technology and the need for sustainable development remain. Using a qualitative approach and secondary data from official documents, government reports, academic journals, and media publications, the study provides a comprehensive understanding of the dynamics and complexities of India's economic diplomacy. Focusing on domestic industry development, energy efficiency, and innovation, India aims to achieve long-term economic sustainability. The findings contribute to the literature on economic diplomacy and offer insights for policymakers to enhance international economic relationships.